2022
DOI: 10.3390/biomedicines10112741
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Cognitive Functions, and Degenerative Dementias: State of the Art

Abstract: There is strong evidence that homocysteine is a risk factor not only for cerebrovascular diseases but also for degenerative dementias. A recent consensus statement renewed the importance and the role of high levels of homocysteine in cognitive decline in several forms of degenerative dementia, such as Alzheimer’s disease. Although the molecular mechanisms by which homocysteine causes cell dysfunction are known, both the impact of homocysteine on specific cognitive functions and the relationship between homocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 189 publications
(300 reference statements)
0
10
0
Order By: Relevance
“…Homocysteine in cells is also removed through the remethylation or transsulfuration pathways. Hyperhomocysteinemia due to the inherited deficiency of cystathionine β-synthase, decreased renal excretion due to impaired renal function, or imbalance of one-carbon metabolism has been well demonstrated to be associated with an increased risk of cardiovascular diseases [ 99 ] and neurocognitive disorders [ 100 ]. In fact, blood homocysteine levels tend to increase with age, which may be associated with an age-dependent decline in global DNA methylation [ 18 ].…”
Section: One-carbon Metabolism Dna Methylation and Agingmentioning
confidence: 99%
“…Homocysteine in cells is also removed through the remethylation or transsulfuration pathways. Hyperhomocysteinemia due to the inherited deficiency of cystathionine β-synthase, decreased renal excretion due to impaired renal function, or imbalance of one-carbon metabolism has been well demonstrated to be associated with an increased risk of cardiovascular diseases [ 99 ] and neurocognitive disorders [ 100 ]. In fact, blood homocysteine levels tend to increase with age, which may be associated with an age-dependent decline in global DNA methylation [ 18 ].…”
Section: One-carbon Metabolism Dna Methylation and Agingmentioning
confidence: 99%
“…The mechanism of homocysteine‐induced dementia is complicated 40 . The link between cognitive deterioration and high homocysteine levels has been explained by many mechanisms 41,42 . Neurotoxicity is also associated with homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“… 40 The link between cognitive deterioration and high homocysteine levels has been explained by many mechanisms. 41 , 42 Neurotoxicity is also associated with homocysteine. Oxidative stress, inflammation, and brain cell loss can result from high homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 6 is also required for the conversion of homocysteine (Hcy) to cysteine and, together with vitamin B 12 and folate (vitamin B 9 ), plays a key role in maintaining physiological plasma levels of Hcy (10–20 mol/L) [ 52 ]. Interestingly, higher Hcy concentrations in the blood are considered a major risk factor for AD, PD, and vascular dementia [ 53 , 54 , 55 ].…”
Section: Vitamins In Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%
“…Clinical studies on AD patients have indicated that lower concentrations of vitamins B 9 and B 12 correlate with high serum Hcy levels [ 88 , 89 ]. As previously mentioned, hyperhomocysteinemia is commonly observed in PD, AD, and MCI cases [ 53 , 54 , 55 ]. The correlation between elevated Hcy concentrations and vitamins B 9 and B 12 deficiency might be explained by taking into account that both vitamins are involved in the methionine/homocysteine cycle [ 90 ].…”
Section: Vitamins In Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%